PENERAPAN KONSELING BEHAVIORAL DENGAN TEKNIK MODELING UNTUK MENGATASI PERILAKU MALAS BELAJAR SISWA KELAS XI SMA NEGERI 1 SEMARANG - Rachmad Djatun; Tri Hartini; Ismah . (Empati-Jurnal Bimbingan dan Konseling, 2014)
The purpose of this reserch is to know activity practice konseling behavior, with modeling teknik to cope with behavior of student in two class at SMA Negeri 1 Semarang in 2012/2013 are lazy to study.From the result of implementation or counseling servise are going to do for 3 times in 3 months, that konseling modeling can make the students are lazy. The fact from the reserchs are geting the different lazy to study behaviour incrise in to more dilligent, the students attained the skors: the student number 05 get skors 95firsly and remove in to 104. The student number 14 get skors 93 firsly and remove in to 107. The students number 32 get skors 94 firsly and remove in to 104. The student number 33 get skors 93 firsly and remove in to105. The student number 34 get skors 96 firstly and remove in to107. The studens number 48 get skors 94 firsly and remove in to 103. The first obigation must do for the student to get the purpose.Keywords: Behavior counseling, modeling, lazy to study